Effects of isometric resistance training and detraining on ambulatory blood pressure and morning blood pressure surge in young normotensives - Baross, A. W.; Kay, A. D.; Baxter, B. A.; Wright, B. H.; McGowan, C. L.; Swaine, I. L. (Frontiers in Physiology, 2022)
Isometric resistance training (IRT) has been shown to reduce resting and ambulatory blood pressure (BP), as well as BP variability and morning BP surge (MBPS). However, there are no data available regarding how long after cessation of IRT these effects are maintained. Therefore, the purpose of this study was to determine the effects of 8 weeks of detraining on resting BP, ambulatory BP and MBPS following 8 weeks of IRT in a population of young normotensive individuals and to further substantiate previously reported reductions in MBPS following IRT. Twenty-five apparently healthy participants with resting BP within the normal range (16 men, age=23±6 years; 9 women, age=22±4 years, resting BP: 123±5/69 ±7 mmHg) were randomly assigned to a training-detraining (TRA-DT, n=13) or control (CON, n=12) group. Resting BP, ambulatory BP and MBPS were measured prior to, after 8 weeks of bilateral leg IRT using an isokinetic dynamometer (4 x 2-minute contractions at 20% MVC with 2-minute rest periods, 3 days/week) and following an 8-week detraining period. There were significant reductions in 24-h ambulatory systolic BP (SBP) and calculated SBP average real variability (ARV) following IRT that were maintained after detraining (pre-to-post detraining, -6±4 mmHg, p=0.008, -2±1.5 mmHg, p=0.001). Similarly, the training-induced decreases in daytime SBP and daytime SBP ARV (pre-to-post detraining, -5±6 mmHg, p=0.001; -2±1.2 mmHg, p=0.001, respectively), MBPS (pre-to-post detraining, -6±9 mmHg, p=0.046) and resting SBP (pre-to-post detraining, -4 ± 6 mmHg, P = 0.044) were preserved. There were no changes in night-time or night-time SBP ARV across all time points (pre-to-post detraining, -1±8 mmHg, p=1.00, -0.7±2.9 mmHg, p=1.00). These results confirm that IRT causes significant reductions in resting BP, ambulatory BP, ambulatory ARV and MBPS. Importantly, the changes remained significantly lower than baseline for 8 weeks after cessation of training, suggesting a sustained effect of IRT.